DOI: 10.29007/1pdv
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impacts on AEC Educators

Abstract: To alleviate the impact of COVID-19 on academia, numerous countries transitioned to electronic or online methods for education delivery. Within the US, during March and/or April 2020, numerous institutions transitioned to Online Learning Environment (OLE). However, very little is known about how the transition to OLE impacted the educators. Thus, the research aimed to determine the impact of OLE transition on AEC educators as per the academic ranks and gender. The study utilized an online survey method with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The transition to OLE was difficult for both students and educators due to numerous factors, including but not limited to the lack of software, hardware, Internet availability (Asgari et al ., 2021), limited experience with teaching in the online environment (Langar et al. , 2022a, b), impact of COVID-19 on mental well-being (UAB, 2020; Brooks et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition to OLE was difficult for both students and educators due to numerous factors, including but not limited to the lack of software, hardware, Internet availability (Asgari et al ., 2021), limited experience with teaching in the online environment (Langar et al. , 2022a, b), impact of COVID-19 on mental well-being (UAB, 2020; Brooks et al.…”
Section: Introductionmentioning
confidence: 99%
“…Technical aspects could impact how individuals perceive their abilities when applying self-efficacy). Further, students and educators (Asgari et al ., 2021; Langar et al ., 2022a) identified a lack of social interaction, which is a dimension of learning self-efficacy (Shen et al ., 2013). In India, training architecture educators, particularly in India, training was identified as a critical for educators success during the pandemic (Varma and Jafri, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Clemson et al ( 2022) identified research productivity as impacted among the pharmacy faculty in research-intensive colleges. Langar et al (2021) studied the impact of OLE on construction educators and found improvements in teaching with OLE while a declining in overall productivity.…”
Section: Epic Series In Built Environmentmentioning
confidence: 99%
“…The most common concerns impacting faculty during Covid-19 Pandemic included 1) limited interaction with the students, 2) background noise while participating in virtual meetings, 3) internet issues, 4) too many conference calls, 5) virtual meetings, and 6) limited work and life separation (Langar et al, 2022b). Further, Langar et al (2021) found that tenured or tenure-track educators were spending less time on research, whereas "non-tenured" spent more time developing and delivering content, resulting in a productivity decline in both research and content delivery. While some research indicates the benefits of working from home (especially during the pandemic), the consensus is that a significant proportion of educators realize research productivity being impacted (Clemson et al, 2022;Iwu et.…”
Section: Epic Series In Built Environmentmentioning
confidence: 99%
See 1 more Smart Citation